Introduction. Women Challenging the Constitution: New Evidence - Black, Naomi; Carbert, Louise (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
This article is more political than legal. Using the approaches identified by feminist institutionalism, it focuses on the interactions between the Canadian Advisory Council on the Status of Women (CACSW) and the Canadian government during the constitutional crisis of 1980-1981. How did the gendered institutions of the federal government facilitate a narrative that, finally, was harmful to the women’s movement in Canada?